Time, scarcity, and abundance - Ghosh, Shubha (Frontiers in Research Metrics and Analytics, 2022)
Scarcity abounds in law just as abundance is subject to law's limitations. This Article builds on legal theory, economics, and social psychology to present the dialectic of scarcity and abundance as they interplay in our relationship to information and time. This Article has made two overarching arguments: one about scarcity, abundance, and regulation generally and a second about time as an instrument of regulation subject to terms of scarcity and of abundance. The first argument is that scarcity and abundance are rhetorical constructs that inform different regulatory institutions. Scarcity traditionally has mapped onto limits on freedom. Abundance, by contrast, props freedom's unlimited potential. Under the language of scarcity, limits promote outcomes, for example through rights to exclude, deprivation of a benefit, or imposition of a burden. Under the language of abundance, identified freedoms promote outcomes through rights of access or rights to use. Scarcity is distinct from absolute deprivation, and abundance, from unbounded and infinite possibility. Each are building blocks understood relative to the goals of institutional design. Furthermore, scarcity and abundance have an intertwined relationship, a dialectic of famine and plenty. Similarly, freedom and limitations coexist each supporting the other. The second argument of this Article is that time as an instrument of regulation illustrates the uses of scarcity and abundance. Time can be regimented to regulate activities such as work, travel, diet, reproductive rights, social relations, and interaction with media. Time can also be liberating, seemingly abundant using perpetuities, technologies for fast forwarding, rewinding, or shifting content, and increases in the velocity of access and movement. Information retrieval, processing, and sharing are connected to time. It is no surprise that reform proposals for the problems confronting the information economy rest up regulation of time. This Article has demonstrated what these reform proposals share is an attempt to make time scarce, to return to perhaps an idealized era of regimented broadcast within an era of multivalent technological means for information creation and dissemination. But imposing scarcity on abundance ignores the deeper challenges of information glut and distortion: how to manage and assess content.